Key Players in the Mutant p53 Team: Small Molecules, Gene Editing, Immunotherapy - Chasov, Vitaly; Mirgayazova, Regina; Zmievskaya, Ekaterina; Khadiullina, Raniya; Valiullina, Aygul; Stephenson Clarke, Joseph; Rizvanov, Albert; Baud, Matthias G. J.; Bulatov, Emil (Frontiers in Oncology, 2020)
The transcription factor p53 is a key tumor suppressor that is inactivated in almost all cancers due to either point mutations in the TP53 gene or overexpression of its negative regulators. The p53 protein is known as the “cellular gatekeeper” for its roles in facilitating DNA repair, cell cycle arrest or apoptosis upon DNA damage. Most p53 mutations are missense and result in either structural destabilization of the protein, causing its partial unfolding and deactivation under physiological conditions, or impairment of its DNA-binding properties. Tumor cells with p53 mutations are generally more immunogenic due to “hot spot” neoantigens that instigate the immune system response. In this review, we discuss the key therapeutic strategies targeting mutant p53 tumors, including classical approaches based on small molecule intervention and emerging technologies such as gene editing and T cell immunotherapy.